Italian culture in the poetry of José Antonio Mazzotti - Valero Juan, Eva (2022)
In the poetic work of José Antonio Mazzotti, a Peruvian author of Italian descent, the presence of the Italian cultural world is a constant that takes shape both in the use of the figure of Dante and the Divine Comedy for the poetization of Peru of the violence of the 1980s, as in mythological references that are updated for a poetic reading of the present. This article aims at analyzing some of the paradigmatic poems of this presence and trace this mythological line, in order to project the presence and relevance of Italy, its culture and its history as a whole, in the poetic work of Mazzotti.